KAJIAN PUSTAKA FORMULASI DAN EVALUASI MIKROKAPSUL SALUT ENTERIK MENGGUNAKAN ACRYL-EZEÂ® & SURETERIC DENGAN METODE PENGGABUNGAN MIKROENKAPSULASI DENGAN EKSTRUSI-SFERONISASI - Santoso, Rahmat; Aliudin, Fiqi (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2020)
Microcapsules were prepared by means of microencapsulation modified by the extrusion-spheronization method. The extrusion-spheronization method is used to cover the shortcomings of the microencapsulation method. The results showed that Acryl-eze and Sureterik can be used in coatings in producing microcapsules. The results of research evaluating the formulation of enteric acetosal coated microcapsules have not resulted in delayed release system that is in accordance with monographic requirements and dissolution profile testing has not shown the elimination stage. The results of the evaluation of the delayed release release system enteric coated microcapsule formulation met the requirements of monograph and dissolution profile test results, except for F3 in buffering conditions. The purpose of this literature review is to examine the enteric-coated microcapsule formulation using Acryl-ezeÂ® & Sureteric by combining microencapsulation and spheronization extrusion methods.